Micro porosity of coated paper affected by modified pigment particles - Možina, Klemen; Franken, Gregor (Journal of Graphic Engineering and Design, 2018)
Expensive synthetic coating materials can be replaced with natural coatings and surface treatment with natural components and additives which are friendlier to the environment and have normally better special surface properties. However, special properties can be obtained with surface functionalization by chemical or surface geometry modification. Beside optical properties, the trends of lightweight materials, i.e. reducing grammage by using nano materials and products (i.e. NMP - N-Methyl-2-Pyrrolidone), lower specific energy requirement and costs, forces increasing of pigments usage. Results of survey showed that surface properties of papers coated with modified ground calcium carbonate (GCC), required for inkjet printing with water-based inks had improved significantly, whereas the increment of printed object has minimum differentiation from the ideal, computer-based character.